{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

t1sample_solutions

# t1sample_solutions - Math 115 001 Test 1 Solutions to...

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Math 115 001 Test 1 - Solutions to Sample Problems Fall 2011 (1) lim x → x 3- 1 x does not exist. lim x →∞ x 3- 2 x 2 + x- 3 x 3 + 5 x = lim x →∞ 1- (2 /x ) + (1 /x 2 )- 3 + (5 /x 2 ) = 1- 0 + 0- 3 + 0 =- 1 3 . lim x →-∞ x 2 + 2 x + 1 5 x 4 + 10 x 2 = lim x →-∞ (1 /x 2 ) + (2 /x 3 ) + (1 /x 4 ) 5 + 10 /x 2 = 5 = 0. [Note that the preceding was done by cancelling the highest power of x , namely x 4 , that appears in either the numerator or denominator. In class, we cancelled out the highest common power, which would be x 2 . Both methods work.] lim x → sin x 2 x = 1 2 lim x → sin x x = 1 2 (1) = 1 2 . [What if the problem is: Find lim x → sin2 x x ] (2) f ( x ) = lim h → √ x + h + 1- √ x + 1 h = lim h → √ x + h + 1- √ x + 1 h √ x + h + 1 + √ x + 1 √ x + h + 1 + √ x + 1 = lim h → ( x + h + 1)- ( x + 1) h ( √ x + h + 1 + √ x + 1) = lim h → h h ( √ x + h + 1 + √ x + 1) = lim h → 1 √ x + h + 1 + √ x + 1 = 1 2 √ x + 1 (3) f ( x ) = x 3 1 x 2 + 1 (2 x ) +3 x 2 ln( x 2 +1) = 2 x 4 ( x 2 + 1) x 2 + 1 +3 x 2 ln( x 2 +1), using the product rule and the chain rule....
View Full Document

{[ snackBarMessage ]}

### Page1 / 3

t1sample_solutions - Math 115 001 Test 1 Solutions to...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online